Pengaruh Penggunaan Media Konkret terhadap Kemampuan Operasi Hitung Dasar dan Motivasi Belajar Matematika Siswa Kelas IV SD - Agustina, Nawang Shinta; Yulianto, Sigit (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study was to analyze the effect of using certain media on the operational skills and motivation to learn mathematics of fourth-grade students at SDN Sumowono, Semarang Regency. This study used a quantitative approach with a correlational design. The subjects of the study were all 34 fourth-grade students at SDN Sumowono. Data collection techniques used questionnaires to increase motivation to learn mathematics, tests to improve basic operational skills, and documentation as a data collection tool. Data analysis was carried out using IBM SPSS Statistics version 27, which included tests of validity, reliability, normality, linearity, correlation between Pearson Product Moments, and significance (t). The results showed that the use of certain media had a positive and significant effect on students' operational skills and motivation to learn mathematics. In addition, basic operational skills had a significant relationship with motivation to learn mathematics. Based on these results, it can be concluded that the use of concrete media in mathematics learning is effective in improving basic arithmetic operations and learning motivation of fourth-grade elementary school students.